An investigation into the determinants of Investment strategy of UK with-profit life office - LI, BO (2008)
This research investigates the investment strategy of UK life offices that have with-profit businesses since the launch of the new regime by Financial Services Authority. A number of determinants of investment strategy are identified and tested over the period of 2005 to 2007 after the launch of the new regime: nature of liability, financial strength, firm size, organizational form and close to new business. Standard multiple regression is used to run the variance of investment activities that explained by the above independent variables. Dependent variables are classified as EBR, PBR, EPBR, BBR, OBR, Non-approved bond ratio and weighted average credit rating index (WACR). Nature of liabilities has found no strong links with bonds but positive influence over EPBR. Financial strength appears to have small effects on EBR and PBR but rather strong positive relationship with bond ratio. Firm closes to new business are found to have negative correlation with EBR and PBR, consistent with our expectation. Organizational form and firm size do not appear to have strong influence on investment strategy.